Advancements and challenges in gene editing for improvement of vegetatively propagated crops - Tripathi, J.N.; Muiruri, S.; Tripathi, L. (Elsevier, 2024)
Gene editing technologies, particularly CRISPR-Cas9, have revolutionized agriculture by offering precise and efficient tools to enhance crop production. The vegetatively propagated crops, crucial for global food security, face challenges such as climate change, pests, and limited genetic diversity. CRISPR-Cas9 enables targeted modifications to improve traits like disease resistance, drought tolerance, and nutritional content, thereby boosting productivity and sustainability. Despite its transformative potential, the adoption of gene editing in vegetatively propagated crops is hampered by technical complexities and regulatory frameworks. This review explores recent advancements, challenges, and prospects of gene editing in vegetatively propagated crops, emphasizing strategies to overcome technical barriers and regulatory constraints. Addressing these issues is essential for realizing the full agricultural potential of gene editing and ensuring food security in a changing global climate.